Cerebral blood flow modulations during preparatory attention and proactive inhibition - Duschek, Stefan; Schüpbach, Daniel (Biological psychology, 2018)
This study investigated cerebral blood flow modulations during task preparation in a precued saccade paradigm. Bilateral blood flow velocities in the middle cerebral arteries were recorded in 48 subjects using functional transcranial Doppler sonography. Video-based eye-tracking was applied for ocular recording. Antisaccade and prosaccade trials were presented in both block-wise and interleaved order. A right dominant flow response arose during task preparation. While the response was stronger during antisaccade than prosaccade trials, the degree of lateralisation did not differ between the two trial types. Direction error rates were higher and latencies were longer for antisaccades than prosaccades. There were no differences between block-wise and interleaved trials in blood flow or performance. The stronger blood flow increases during antisaccade than prosaccade preparation reflects the complexity of the upcoming task demands as well as proactive inhibition. The right hemispheric lateralisation may be attributed to preparatory attention independent of demands on inhibitory control.